Ecclesiastes - O'Donnell, Douglas Sean, 1972- (Phillipsburg, New Jersery : P & R Publishing, 2014)
Douglas O Donnell shows, in this redemptive-historical, biblical, practical, and expositional commentary, that Ecclesiastes answers two key questions that worry everybody in the depths of their minds. The first is "What does man gain from all the toil at which he toils under the sun?" the answer being "nothing." The second follows: "In light of such vanity the fact that our work and knowledge and pleasures and possessions are ultimately made futile by death how then should we live this temporary life under the sun?" The answer is surprisingly simple: we are to abandon human illusions of self-importance, put aside all pretense of pride, and embrace divine wisdom. "The Preacher" of Ecclesiastes says that this is "the end of the matter; all has been heard. Fear God and keep his commandments, for this is the whole duty of man" (12:13). O Donnell explains how these two key ideas inform the text of Ecclesiastes and the practical instruction that flows from them. -- Amazon.com
The end of Ecclesiastes : an introduction (Ecclesiastes 1:1-2) -- Why I wake early (Ecclesiastes 1:3-11) -- A crack in the window of wisdom (Ecclesiastes 1:12-18) -- The hollow house of hedonism (Ecclesiastes 2:1-11) -- Enjoyment east of Eden (Ecclesiastes 2:12-26) -- The terrific truth about time (Ecclesiastes 3:1-15) -- Sights under the sun (Ecclesiastes 3:16-22) -- It is not good for the children of man to be alone (Ecclesiastes 4:1-16) -- Sandals off, mouth shut (Ecclesiastes 5:1-7) -- Grevious evils, great joys (Ecclesiastes 5:8-6:9) -- Instructions from the grave (Ecclesiastes 6:10-7:14) -- Finding the fear of God in a crooked world (Ecclesiastes 7:15-29) -- Living within the limits to the limit (Ecclesiastes 8:1-15) -- What to know about knowing nothing (Ecclesiastes 8:16-9:12) -- Dead flies, a serpent's bite, and twitter (Ecclesiastes 9:13-10:20) -- Before the evil days come (Ecclesiastes 11:1-12:8) -- Repining restlessness (Ecclesiastes 12:9-14).
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries